2010
DOI: 10.1007/s00383-010-2626-1
|View full text |Cite
|
Sign up to set email alerts
|

Urological problems or fecal continence during long-term follow-up of patients with anorectal malformation

Abstract: Urinary system anomalies in patients with ARM are at least as serious and complex as gastrointestinal system anomalies and create more problems than fecal incontinence during long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Previous studies showed an incidence ranging from 14 to 27% [9, 10, 15, 22]. In our population, vesico-ureteral reflux was mostly encountered performing a voiding cysto-urethrography (VCUG).…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies showed an incidence ranging from 14 to 27% [9, 10, 15, 22]. In our population, vesico-ureteral reflux was mostly encountered performing a voiding cysto-urethrography (VCUG).…”
Section: Discussionmentioning
confidence: 78%
“…The consequences of these anomalies can be more problematic than the anorectal malformation itself, leading in the most severe cases to urinary incontinence or deterioration of renal function. 1,2 Motor and sensory signs can develop later, and sphincter abnormalities may appear only once the child is out of diapers.…”
mentioning
confidence: 99%
“…15 We came across only one study from Turkey on the QoL in children with anorectal malformations. 16 HD is characterized by partial or total absence of ganglion cells in the nerve plexuses of the distal bowel, of varying levels. IA is a deformity of anorectum,with a varying severity from a relatively simple covered anus to the most complex defect of persistent cloaca.…”
mentioning
confidence: 99%